Clinical characteristics and outcome of drug-induced liver injury in the older patients: from the young-old to the oldest-old - Weersink, Rianne A.; Álvarez-Álvarez, Ismael; Medina-Cáliz, Inmaculada; Sanabria-Cabrera, Judith Adriana; Robles-Díaz, María Mercedes; Ortega-Alonso, Aida; García-Cortés, Miren; Bonilla, Elvira; Niu, Hao; Soriano, German; Jiménez-Pérez, Miguel; Hallal, Hacibe; et al. (Wiley, 2020)
Old patients with hepatotoxicity have been scarcely studied in idiosyncratic drug-induced liver injury (DILI) cohorts. We sought for the distinctive characteristics of DILI in older patients across age groups. A total of 882 DILI patients included in the Spanish DILI Registry (33% ≥65 years) were categorized according to age: “young” (<65y); “young-old” (65-74y); “middle-old” (75-84y); and “oldest-old” (≥85y). All elderly groups had increasingly higher comorbidity burden (p<0.001) and polypharmacy (p<0.001). There was a relationship between jaundice and hospitalization (p<0.001), and both were more prevalent in the elderly age groups, especially in the oldest-old (88% and 69%, respectively) and the DILI episode was more severe (p=0.029). The proportion of females decreased across age groups from the young to the middle-old, yet in the oldest-old there was a distinct female predominance. Pattern of liver injury shifted towards cholestatic with increasing age among top culprit drugs amoxicillin- clavulanate, atorvastatin, levofloxacin, ibuprofen, and ticlopidine. The best cut-off point for increased odds of cholestatic DILI was 65y. Older patients had increased non-liver related mortality (p=0.030) as shown by the predictive capacity of MELD (OR=1.116; p<0.001), and comorbidity burden (OR=4.188; p=0.001) in the 6-month mortality. Older patients with DILI exhibited an increasingly predominant cholestatic phenotype across a range of culprit drugs other that amoxicillin-clavulanate, with increased non-liver related mortality and require a different approach to predict outcome. The oldest DILI patients exhibited a particular phenotype with more severe DILI episodes and need to be considered when stratifying older DILI populations.
Keywords: Hígado - Enfermedades; Drug-induced liver injury; Elderly; Oldest-old; Cholestatic; Comorbitity; Mortality